2001
DOI: 10.1111/j.0014-3820.2001.tb00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consequences of Polygyny and Social Structure in an Indian Fruit Bat, Cynopterus Sphinx. Ii. Variance in Male Mating Success and Effective Population Size

Abstract: Abstract. Variance in reproductive success is a primary determinant of genetically effective population size (N e ), and thus has important implications for the role of genetic drift in the evolutionary dynamics of animal taxa characterized by polygynous mating systems. Here we report the results of a study designed to test the hypothesis that polygynous mating results in significantly reduced N e in an age-structured population. This hypothesis was tested in a natural population of a harem-forming fruit bat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 67 publications
2
96
0
Order By: Relevance
“…Lim et al (2008) suggested that the distribution pattern of C. sphinx should be investigated as little is known about the current distribution of this species in Malaysia. Clinal variation in terms of size of this species was discussed by Storz et al (2001) and our observations (unpublished data) indicate that C. sphinx is not highly adaptable in Peninsular Malaysia incongruent with observations of Bates et al (2008b). Although widespread the abundance of this species is determined by the type of vegetation sampled (Campbell et al 2006).…”
Section: Balionycteris Maculatasupporting
confidence: 71%
“…Lim et al (2008) suggested that the distribution pattern of C. sphinx should be investigated as little is known about the current distribution of this species in Malaysia. Clinal variation in terms of size of this species was discussed by Storz et al (2001) and our observations (unpublished data) indicate that C. sphinx is not highly adaptable in Peninsular Malaysia incongruent with observations of Bates et al (2008b). Although widespread the abundance of this species is determined by the type of vegetation sampled (Campbell et al 2006).…”
Section: Balionycteris Maculatasupporting
confidence: 71%
“…In this species, males sire 29% of the pups in their harem (Heckel et al 1999). In other species, this value averages around 60% but can range up to 100% in individual harems (Storz et al 2001b;Ortega et al 2003). In comparison, male birds, such as tree swallows, remain socially monogamous in spite of 70% or more extra-pair copulations by the females (Kempenaers et al 1999).…”
Section: Male Point Of Viewmentioning
confidence: 84%
“…At the same time, sheltering another male's pup may not incur additional costs, if the nest-holder can sire the mother's next offspring. Reproductive success of male C. sphinx depends on colony structure during the previous post-partum estrus rather than current parturition (Storz et al 2001b), and the same may be true for male L. silvicolum. We show that relatedness of males with pups in their nest is high, indicating that they mate with the females that roost with them, thus justifying roost-making.…”
Section: Male Point Of Viewmentioning
confidence: 96%
“…The results from AMOVA reflected extreme heterozygote deficiency among tumour-affected populations, possibly due to either a Wahlund effect caused by sampling functionally independent social reproductive harems that has confounded the interpretation of Wright's F IS (Storz et al 2001). The 'within population' inbreeding estimate (f = FIS) or value of deficit of heterozygotes.…”
Section: Discussionmentioning
confidence: 99%